Evaluating carbon stocks in soils of fragmented Brazilian Atlantic Forests (BAF) based on soil features and different methodologies - Guerrini, Iraê Amaral [UNESP]; da Silva, Jaqueline Pinheiro [UNESP]; Lozano Sivisaca, Deicy Carolina [UNESP]; de Moraes, Felipe Góes [UNESP]; Puglla, Celso Anibal Yaguana [UNESP]; de Melo Silva Neto, Carlos; Barroca Silva, Rafael [UNESP]; Pereira Justino, Sérvio Túlio [UNESP]; Roder, Ludmila Ribeiro; James, Jason Nathaniel; Capra, Gian Franco; Ganga, Antonio (Springer Nature, 2024)
Brazil’s Atlantic Forest (BAF) is a highly fragmented, strategic environmental and socio-economic region that represents the fourth biodiversity hotspot while also producing many commodities that are exported globally. Human disturbance plays a pivotal role as a driver of BAF’s soil dynamics and behaviors. The soils under Late Primary and Secondary Semideciduous Seasonal Forests (LPSF and LSSF) were characterized by high to moderate resilience, with improved chemical properties as human disturbance decreased. The Transitional Forest to Cerrado (TFC) had the worst soil conditions. Disturbed Primary and Secondary Semideciduous Seasonal Forests (DPSF and DSSF) represent a transitional stage between LPSF/LSSF and TFC. Accordingly, SOCs stocks increased from TFC << DPSF, DSSF < LPSF, LSSF. In BAF soils, to avoid unreliable data, SOCs measurements should be (i) conducted to at least 1 m soil depth and (ii) quantified with a CHN analyzer. Human disturbance strongly affected the positive feedback between vegetation succession, SOCs, and soil nutrition. Soil development decreased as human disturbance increased, thus negatively affecting SOCs. Soils in the BAF require a long time to recover after the end of human disturbance, thus suggesting that preservation strategies should be prioritized in remnant BAF fragments.